Kajian Potensi Desa sebagai Peningkatan Ekonomi Masyarakat Desa Monggol Kecamatan Saptosari Kabupaten Gunung Kidul - Meriliandi, Kadek Wahyu Fitriaputi; Sijabat, Okthalia Larasati; Tanuwijaya, Shania Angeline; Modjanggo, Irmalani; Indrakusuma, F. X. Bagas; Saragih, Nia Handayani; Marlissa, Morgan Gerhardt; Irawan, Florencia Irene; Radjab, Ukhra Niyantama; Hadinata, Michael Evan; Widiastiani, Nindry Sulistya (Jurnal Atma Inovasia, 2021)
To improve the prosperity of the people at Monggol Village, there needs to be an increase in agricultural potential, cultural potential, and tourism potential of Monggol Village. Kuliah Kerja Nyata 78 Society 5.0 Atma Jaya Yogyakarta University of group 36, a work program was produced to increase the potential of monggol village in improving the economy of monggol village community. Types of research conducted based on social facts. Primary data is data obtained directly from researchers through Searching Google by researchers for the specific purpose of solving the problems they are dealing with. Secondary data collected comes from literature, journals, articles and also the Internet (Searching Google). Data obtained through Searching Google and also data from the Central Statistics Agency is then analyzed qualitatively as stated in Google Docs, then understood and compiled the data that has been collected through Whatsapp Group or Meet Microsoft Teams. Based on the data that can be later in the analysis, it is drawn conclusions in inductive thinking methods. Conclusions in this work program will be carried out increasing the potential of tourism villages, namely Jlumbang Lake and Human Resources Improvement in Agricultural Potential, namely the manufacture of Cassava Cake (Sicak) to improve the economy of the people of Monggol Village, Saptosari District, Gunung Kidul Regency.